Skeletal muscle fiber analysis by atmospheric pressure scanning microprobe matrix‐assisted laser desorption/ionization mass spectrometric imaging at high mass and high spatial resolution. Issue 11 (15th June 2016) - Tsai, Yu‐Hsuan; Bhandari, Dhaka Ram; Garrett, Timothy J.; Carter, Christy S.; Spengler, Bernhard; Yost, Richard A.
Abstract : Skeletal muscles are composed of heterogeneous muscle fibers with various fiber types. These fibers can be classified into different classes based on their different characteristics. MALDI mass spectrometric imaging (MSI) has been applied to study and visualize different metabolomics profiles of different fiber types. Here, skeletal muscles were analyzed by atmospheric pressure scanning microprobe MALDI‐MSI at high spatial and high mass resolution.